Pastas compósitas cimento/sílica/polímero para cimentação de poços de baixa profundidade sujeitas à injeção de vapor - Fernandes, Maria Roseane de Pontes (2009)
The production of heavy oil fields, typical in the Northeastern region, is commonly stimulated by steam injection. High bottom hole temperatures are responsible not only for the development of deleterious stresses of the cement sheath but also for cement strength retrogression. To overcome this unfavorable scenario, polymeric admixtures can be added to cement slurries to improve its fracture energy and silica flour to prevent strength retrogression. Therefore, the objective of the present study was to investigate the effect of the addition of different concentrations of polyurethane (5-25%) to cement slurries containing 40% BWOC silica flour. The resulting slurries were characterized using standard API (American Petroleum Institute) laboratory tests. In addition to them, the mechanical properties of the slurries, including elastic modulus and microhardness were also evaluated. The results revealed that density, free water and stability of the composite cement/silica/polyurethane slurries were within acceptable limits. The rheological behavior of the slurries, including plastic viscosity, yield strength and gel strength increased with the addition of 10% BWOC polyurethane. The presence of polyurethane reduced the fluid loss of the slurries as well as their elastic modulus. Composite slurries also depicted longer setting times due to the presence of the polymer. As expected, both the mechanical strength and microhardness of the slurries decreased with the addition of polyurethane. However, at high bottom hole temperatures, the strength of the slurries containing silica and polyurethane was far superior than that of plain cement slurries. In summary, the use of polyurethane combined with silica is an interesting solution to better adequate the mechanical behavior of cement slurries to heavy oil fields subjected to steam injection